2009
DOI: 10.1111/j.1440-1681.2009.05184.x
|View full text |Cite
|
Sign up to set email alerts
|

DILATED CARDIOMYOPATHY WITH HYPERTENSION: PREVALENCE AND RESPONSE TO HIGH‐DOSE β1‐ADRENOCEPTOR ANTAGONIST THERAPY

Abstract: 1. The aim of the present study was to investigate the prevalence of hypertension in patients with dilated cardiomyopathy (DCM) and to determine the tolerance and efficacy of a high dose of the β1-adrenoceptor antagonist metoprolol in the long-term treatment of DCM patients. 2. The prevalence of hypertension in DCM patients (n = 362) and age-matched controls (n = 401) was evaluated and compared. To investigate the effects of metoprolol, DCM patients were divided into hypertensive (DCM-H) or normotensive (DCM-N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Hypertension is a growing health issue that leads to many cardiovascular complications, and the prevalence of hypertension is higher in patients with NIDCM than in the general population. 11 Previous studies have shown that hypertension alone can lead to myocardial dysfunction, myocardial fibrosis, and LV remodeling. 24,25 However, little is known about the impact of hypertension on LV strain and remodeling in patients with NIDCM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypertension is a growing health issue that leads to many cardiovascular complications, and the prevalence of hypertension is higher in patients with NIDCM than in the general population. 11 Previous studies have shown that hypertension alone can lead to myocardial dysfunction, myocardial fibrosis, and LV remodeling. 24,25 However, little is known about the impact of hypertension on LV strain and remodeling in patients with NIDCM.…”
Section: Discussionmentioning
confidence: 99%
“…10 A previous study indicated that the prevalence of hypertension is higher in patients with NIDCM than in age-matched controls. 11 It has been reported that hypertension is an important risk factor for adverse outcomes in patients with NIDCM, and NIDCM patients comorbid with hypertension have been shown to have a higher risk of sustained ventricular arrhythmias. 12 Thus, considering the poor prognosis among NIDCM patients with hypertension, it would be important to determine the effects of hypertension on LV alterations in NIDCM patients.…”
mentioning
confidence: 99%
“…Clinical trials have shown that hypertension is one of the potential risk factors for DCM. [ 1 2 ] Considering the central role of mitochondria in the production of energy and reactive oxygen species (ROS), mutations in mitochondrial DNA (mtDNA) are believed to affect the pathogenesis of hypertension. [ 3 ] Evidence supports the notion that somatic mtDNA damage is a good predictor of hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Bagger et al during 2 year observation had found out only 2 cases of DCMP accompanied by EH per 41 cases of morphologically proved DCMP. But Zheng X. et al, 2009 at his paper demonstrated that the prevalence of arterial hypertension among DCMP patients is higher than in the same group without hypertension. Our data suggested that combination of DCMP and EH is very rare.…”
Section: Discussionmentioning
confidence: 98%